The Adapting city. Resilience through water design in Rotterdam - Errigo, Maurizio Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The Netherlands is a fragile and vulnerable land; dutch landscape consists of a dense network of polders characterized by key elements such as dams, windmills and farms; it is a unique landscape but, at the same time, is very fragile and constantly changing; spatial planning is very important, just as important is the resilience of the system and its adaptation to climate change. Rotterdam is a delta city and, in a period of heavy climate change, it will experiment more extreme weather conditions, such as heavier rainstorms, longer periods of drought and more heat waves, as well as higher water levels in the river Meuse; so is important to know that it is a deep vulnerable city and need right strategies to overcome the problem and to be adapted to conseguences of climate change. Resilience has been under the attention of the municipality for about fifteen years; Rotterdam is the inspiring example to other delta cities around the world going through a sustainability approach; as a green city is an attractive and resilient city where people love to live, work and relax; sustainability is an integral part of all area development projects in Rotterdam; sustainable areas are future-proof areas with good living conditions. In Rotterdam, architects and urban designers are finally responding to the threats of rising sea levels by "welcoming the water" into city, so the waterscape is becoming a new paradigm of spatial planning; Rotterdam is striving to become a climate proof city that will be safe and attractive to inhabitants, visitors and businesses, and will remain so in the future. A healthy delta city in which it is pleasant to live, work and spend leisure time.